Komparasi Kinerja Interior Gateway Protocol Berbasis Distance Vector dan Link State pada Arsitektur Video Streaming Berbasis Wireless Network - Jamaluddin; Rohmat Gunawan; Firmansyah Maulana Sugiartana Nursuwars (Jurnal Terapan Teknologi Informasi, 2025)
The rapid growth of video streaming services necessitates a reliable network architecture to guarantee Quality of Service (QoS). Inter-network connectivity is achieved through routing technologies, particularly the Interior Gateway Protocol (IGP), which includes dynamic protocols such as the Distance Vector-based RIPv2 and the Link State-based OSPF. This research aims to analyze and compare the performance of the RIPv2 and OSPF routing protocols within a wireless video streaming architecture. The research methodology employs the PPDIOO (Plan, Prepare, Design, Implement, Operate, Optimize) approach developed by Cisco. Testing was conducted under three scenarios: normal conditions, with interference, and with a main path cutoff. Under normal conditions, OSPF demonstrated superiority with a throughput of 2,6277 Mbps, a packet loss of 1,17%, a delay of 3,128 ms, and a jitter of -0,000334156 ms, outperforming RIPv2. When subjected to interference, OSPF maintained its lead with a throughput of 2,5735 Mbps and a packet loss of 3,18%; however, RIPv2 showed a lower jitter value in this scenario. The main path cutoff scenario revealed OSPF's significant superiority. OSPF's throughput was recorded at 1.8014 Mbps, whereas RIPv2's was only 0,6514 Mbps. Furthermore, OSPF's packet loss (31,70%), delay (4,568 ms), and jitter (-0,702716406 ms) were substantially lower than those of RIPv2, which experienced drastic performance degradation. The research findings consistently indicate that OSPF delivers superior, more stable, and efficient performance in maintaining the Quality of Service for video streaming across various network conditions.